A visual environment for specifying global reduction operations. (8th August 2005) - Roxas, Robert R.; Mirenkov, Nikolay N.
This paper presents an approach to specifying the different types of global reduction operations without laboriously coding the source code using the traditional textual approach. We use the visual environment provided by the system called active knowledge studio (AKS) to specify, modify, view, or run the specification. As a background, we give an overview of the AKS system and the main technique being employed that is using 'CyberFilms' in building programs. Although the main focus of this paper is to show how to override at the lowest level the default parameters supplied by the system, we also include a sufficient background about the higher levels so that the reader can relate the lowest level with the other higher levels in the hierarchy of specification. In general, this paper discusses how to specify global reduction operations using a language of micro-icons and shows how the visual programming environment supports the manipulation with these micro-icons.